Liquid Racism and Critical Literacy: Exploring Postgraduate Students’ Perspectives - Τσάμη Βάσια; Σκούρα Ειρήνη; Τσάκωνα Βίλλυ; Αρχάκης Αργύρης (Education Sciences, 2025)
In this article, we attempt to explore the opinions and the concerns of a group of postgraduate students regarding the critical teaching proposals introduced during a training seminar. This seminar was conducted within the context of a research project aiming to undig the racist messages that are reproduced implicitly within anti-racist discourse. Specifically, our sample consisted of 19 postgraduate students who had an academic and/or professional background either in the education or in the management and care of migrant-refugee groups. To implement such proposals, it is crucial to examine the perspectives and concerns of those involved in the educational process. Our findings show both positive attitudes and reservations among participants.